WASTE UTILIZATION TRAINING ABOUT STYROFOAM BECOME A BATAKO IN THE SCAVENGER WASTE COMMUNITY IN PALOPO CITY: STYROFOAM BECOME A BATAKO - Indra Amanah; Miftahul Jannah; Ishak Ishak (STIKes Mandala Waluya Kendari, 2021)
Background: The amount of waste that is not processed and classified as non-biodegradable waste such as Styrofoam, well managed household waste is 36.8%. The amount of waste that is not properly managed is 63.2% of the total weighted waste of 282,654 tonnes. Lack of training for scavengers and the community has resulted in a large amount of stytrofoam waste not being used. Methods: The purpose of this study was to assess the effect of training on using Styrofoam waste into bataco. This research is a pre-experimental study with a one group pre testpost test design, conducted a pretest, then given treatment in the form of training and practice recycling styrofoam into concrete blocks. After that, within a period of approximately 1 month after treatment, a posttest is carried out to measure again. The respondents were trash scavengers, amounting to 83 people. Results: The test results in this study indicate that there is an effect of training on the use of Styrofoam waste into concrete blocks in the garbage scavenger community in Palopo City with a value of p = 0.000. Conclusion: Styrofoam can be modified to become concrete clocks. This can reduce the garbage waste in the community in Palopo City